Assessment of Hip Translation In Vivo in Patients With Femoracetabular Impingement Syndrome Using 3-Dimensional Computed Tomography - Gregory L. Cvetanovich, M.D; Edward C. Beck, M.D., M.P.H; Peter N. Chalmers, M.D; Alejandro A. Espinoza Orías, Ph.D; Michael D. Stover, M.D; Nozomu Inoue, M.D., Ph.D; Shane J. Nho, M.D., M.S (Elsevier, 2020)
Purpose: To determine the 3-dimensional (3D) in vivo hip translation in patients with symptomatic femoroacetabular impingement syndrome (FAIS) using 3D computed tomography (CT) models with the hip in neutral and FABER (flexion, abduction, and the external rotation) positions and to identify patient predictors associated with the degree of hip translation. Methods: Seventy-eight patients with FAIS and cam lesions underwent CT scans in neutral and FABER positions. Demographics including age, sex, and body mass index (BMI) were recorded for each patient. The cam deformity was characterized both in plain x-ray film and 3D. Translation between both positions was calculated using a validated high-precision 3D-3D registration technique. Univariate and multivariate regression analyses sought factors correlated with translation. Results: The mean age of the patients included in the analysis was 36.3 ± 9.2 years, with 51% of the study group being female. The mean 3D femoral head center translation was 0.84 ± 0.37 mm, decomposed into vectors on standard anatomical directions as 0.13 ± 0.58 mm medial, 0.10 ± 0.54 mm posterior, and 0.08 ± 0.46 mm inferior. Multivariate analysis demonstrated that total translation was associated with larger alpha angles (β = 0.014; 95% confidence interval [CI] 0.003-0.024; P = .013), and greater BMI (β = 0.033; 95% CI 0.001-0.065; P = .042). Furthermore, posterior-inferior translation was associated with BMI (β = 0.032; 95% CI 0.003-0.061; P = .031), whereas medial-lateral translation is associated with the female sex (β = 0.388; 95% CI 0.124-0.634; P = .002), and smaller head radius (β = -0.068; 95% CI -0.128 to -0.007; P = .029). Conclusions: As a provocative maneuver, FABER positioning in patients with FAIS resulted in an average measurable translation of the femoral head center in the posterior, medial, and inferior direction. Factors including sex, BMI, and alpha angle predicted the degree of translation. Clinical Relevance: The current study demonstrates that there is measurable hip translation between the neutral and FABER positions in patients with symptomatic FAIS, which may cause hip microinstability. Furthermore, the study found an association between hip translation and both modifiable and nonmodifiable factors. This may indicate the need for more comprehensive preoperative surgical planning, intraoperative dynamic examination of the hip, and consideration of capsular plication in certain patients.